Guiding pedagogical change: an implementation template for effective faculty development - Nuria Lopez; Søren Baltzer Rasmussen (Journal of Learning Development in Higher Education)
This communication presents the Implementation Template developed for a faculty development workshop at the Educational Development and Quality unit of the Copenhagen Business School (CBS), Denmark. The workshop focuses on the implementation of research-based strategies to enhance student learning. The template, shared in this piece for the learning development community to use or adapt, was designed to support faculty by prompting reflection, guiding peer conversations, and identifying relevant strategies to better support student learning in specific teaching contexts. The template has proved to be effective to help faculty self-assess their teaching practice and develop feasible implementation plans for learning enhancement in their courses.